2015
DOI: 10.1016/j.electacta.2015.04.137
|View full text |Cite
|
Sign up to set email alerts
|

On the use of carbon black loaded nitrogen-doped carbon aerogel for the electrosorption of sodium chloride from saline water

Abstract: Highly micro-mesoporous carbon electrodes have been synthesized by the polycondensation of resorcinol-formaldehyde-melamine mixtures in the presence of a carbon conductive additive.The materials showed high surface functionalization (N-and O-groups) provided by the precursors. Despite the low amount used, the conductive additive had a marked effect on the porosity of the aerogels; for a given series, the carbon black loaded materials showed similar micropore volumes and a more developed mesoporosity than the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…In a previous study we reported the two-step synthesis of N-doped carbon aerogels based on the prepolymerization of melamine-resorcinol-formaldehyde (MRF) mixtures [26,27]. Regardless of the solution pH and M/R molar ratio, the hydrogels prepared by the conventional one-step route displayed essentially a microporous character, as opposed to the meso-/macroporous network of those prepared upon the prepolymerization of the precursors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we reported the two-step synthesis of N-doped carbon aerogels based on the prepolymerization of melamine-resorcinol-formaldehyde (MRF) mixtures [26,27]. Regardless of the solution pH and M/R molar ratio, the hydrogels prepared by the conventional one-step route displayed essentially a microporous character, as opposed to the meso-/macroporous network of those prepared upon the prepolymerization of the precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Organic hydrogels are mechanically reinforced upon carbonization at high temperature to render denser carbon gels, that become more rigid (although typical Young modules are still a factor of 100–1000 lower than those of silica glass) but their deformation capacity decreases [9,20,24]. In a previous study we reported the good electrochemical performance of binderless monolithic aerogel electrodes over powdered materials due to the combination of a nanoporous structure interconnected with a macroporous network [26,27,28]; their technological implementation at large scale was, however, limited due to the large shrinkage and deformation of the pieces after the carbonization; the contact between the bent monolithic electrodes and the current collector was compromised, leading to important efficiency losses due to resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature on electrosorption mainly focused on electrode development, and was mostly for specific applications [ 13 , 14 , 15 ]. Porous carbons are often the choice of materials for electrosorption as they combine a high surface area and good electrical conductivity [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for the conductivity, it is mainly controlled by the presence of the carbon black (i.e., 2.1 and 7.7 mS/cm for C-MRF1 and C-MRF1-B; 1.0 and 3.9 mS/cm for C-RF1 and C-RF1-B; 2.2 and 4.3 mS/cm for C-MRF2-D and C-MRF1-BD, respectively); 5 after etching off the diatomite (insulator) the electrodes present conductivity values closed to those prepared without the siliceous additive, although differences also depend on the formulations (ca. N-doped aerogels display higher conductivity than RF ones) [4,5]. In summary, we have fabricated monolithic carbon aerogels with improved mechanical properties while maintaining outstanding porous features and improved electrical conductivity provided by the carbon black additive [4].…”
mentioning
confidence: 99%
“…The usually fragile hydrogels are mechanically reinforced upon carbonization as they become more rigid with increased Young modules [2,3], but their deformation capacity decreases. In previous works we have reported the preparation of carbon aerogels using various precursors with enhanced conductivity and chemical resiliency to oxidation [4,5]. Despite the good electrochemical performance, the use of monolithic electrodes was limited due to the large shrinkage and deformation of the pieces after carbonization -leading to densification of the matrix-[5]; this is a challenge for electrochemical applications where the contact between the electrode material and the current collector is crucial to avoid efficiency losses due to resistance.…”
mentioning
confidence: 99%